Urban Planning and Sustainable Development of Tourism in World Heritage Site, LuangPrabang Town - SOMSAMON , Vilayphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
This paper investigates the urban planning and sustainable development of tourism in World Heritage Site, Luang Prang town. Since the Lao PDR was opened to international tourists in October 1989, the tourism development sector has played a very important role in the socioeconomic development and poverty reduction in Laos. This paper inspects the impact of tourism development in terms of economic, society, and environment, to explore for policies and strategies of government for urban planning of sustainable development of tourism in world heritage site of Luang Prabang town, then propose applicable recommendations to ensure the sustainable development of tourism in Luang Prabang. The primary and secondary data integrated into this work together with observed and interviewed with the tourism-related government officers, some private tourism business owners, and local people. The result we found that since Luang Prabang was appointed to be a World Heritage by UNESCO in 1995, the number of visitors increased dramatically. Luang Prabang also awarded accepted to be the Green and Peaceful Town, no smoking town. With regard to its provincial tourism resources still has virtually untouched natural beauty and biological diversity, historical sites. Tourism development has surely effect on both positive and negative to Luang Prabang as: Economic, Social, and Environment. Therefore, Luang Prang provincial, as well as Lao government, had to pay attention and making policy, strategy and urban planning for the preserve Luang Prang as a World heritage site and other side is for sustainable development of tourism in Luang Prabang. On earlier of 2011 local committees agree to manage Luang Prabang town into 8 important zones as PSMV:ZPP, UB: villages surrounding PSMV, UR: villages of the river bank, UC: villages of mountain, A: airport, NC: Mountains, NA: rice fields and NR: riverbank.